Polydactyly Of The Foot Repair With Circumferential Racquet-Shaped Incision Technique And Collateral Ligament Reconstruction: Case Report And Literature Reviews - Subarno, Saktrio D.; Ibnu Ikhsan, M. Idris (Lingkar Studi Bedah Plastik Foundation, 2019)
Introduction: Polydactyly of the foot is the most common anomaly in congenital diseases. This abnormality is characterized by the presence of additional digits outside the normal complement of the foot. Polydactyly has reported about 1 in 1,000 births. The Watanabe classification is used in assessing polydactyly in the feet as a fifth ray duplication. Various operating techniques can sometimes be an option. Each method has advantages and disadvantages that can be considered in the selection of surgical in the correction polydactyly. Patient and Method: we report a case of polydactyly of the foot reconstruction using circumferential racquet-shaped incision, osteotomy and collateral ligament reconstruction that was carried out at Bahteramas Hospital, Kendari. A circumferential racquet-shaped incision design was performed over the sixth MTP joint. Complete excision of the lateral sixth toe was performed, followed by osteotomy of the fifth metatarsal lateral head with a micro-sagittal oscillating saw. The collateral ligament was reconstructed using ligamentoperiosteal flap and fixed using syringe needle to replace K-Wire. Result : After postoperative control for 3 months the patient was declared good wound healingConclusion: Optimal surgical planning, good patient orientation and surgical techniques that are carefully considered are essential for optimal results. Herein, we report a case of polydactyly and racquet shaped incision technique performed to reconstruct the polydactyly.